Popular music & society. - Longhurst, Brian (Polity, 2014)
The third edition of Popular Music and Society is fully revised and updated, deftly exploring the study of popular music in the context of wider debates in sociology and media and cultural studies. Astute and accessible, it continues to set the agenda for research and teaching in this area. The book begins by examining the ways in which popular music is produced, before moving on to explore its structure as text and the ways in which audiences understand and use music. Packed with up-to-date examples and data on the contemporary production and consumption of popular music, the book includes overviews and critiques of theoretical approaches to this exciting area of study and outlines the most important empirical studies which have shaped the discipline. Topics covered include: